2009
DOI: 10.1107/s0907444909044175
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray structure ofSalmonella typhimuriumuridine nucleoside phosphorylase complexed with 2,2′-anhydrouridine, phosphate and potassium ions at 1.86 Å resolution

Abstract: Uridine nucleoside phosphorylase is an important drug target for the development of anti-infective and antitumour agents. The X-ray crystal structure of Salmonella typhimurium uridine nucleoside phosphorylase (StUPh) complexed with its inhibitor 2,2'-anhydrouridine, phosphate and potassium ions has been solved and refined at 1.86 A resolution (R(cryst) = 17.6%, R(free) = 20.6%). The complex of human uridine phosphorylase I (HUPhI) with 2,2'-anhydrouridine was modelled using a computational approach. The model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Our understanding of the fundamental catalytic mechanisms underlying UPP activity was founded on the structural analysis of bacterial UPPs, first with E. coli UPP (Morgunova et al, 1995; Burling et al, 2003; Caradoc-Davies et al, 2004; Bu et al, 2005) followed by research on the closely-related S. typhimurium homologue (Dontsova et al, 2005; Lashkov et al, 2009, 2010). Only recently have multiple structures of the human enzyme, hUPP1 (Roosild et al, 2009; Roosild and Castronovo, 2010), its bovine homologue, bUPP1 (Paul et al, 2010), and a UPP from the parasitic protozoa, Trypanosoma brucei (Larson et al, 2010), revealed key differences between prokaryotic and eukaryotic variations of this enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the fundamental catalytic mechanisms underlying UPP activity was founded on the structural analysis of bacterial UPPs, first with E. coli UPP (Morgunova et al, 1995; Burling et al, 2003; Caradoc-Davies et al, 2004; Bu et al, 2005) followed by research on the closely-related S. typhimurium homologue (Dontsova et al, 2005; Lashkov et al, 2009, 2010). Only recently have multiple structures of the human enzyme, hUPP1 (Roosild et al, 2009; Roosild and Castronovo, 2010), its bovine homologue, bUPP1 (Paul et al, 2010), and a UPP from the parasitic protozoa, Trypanosoma brucei (Larson et al, 2010), revealed key differences between prokaryotic and eukaryotic variations of this enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…These latter residues, which are key to binding the benzyl modification of high affinity inhibitors such as BAU, are also the only distinguishing active site residues when comparing eukaryotic and prokaryotic enzymes (equivalent E. coli residues are Ile 220, Val221 and P229). This is an important consideration when contemplating generating selectivity in such competitive inhibitors between the two enzymes, as would be needed for the development of effective antibiotics targeting only bacterial homologues of this protein [19].…”
Section: Resultsmentioning
confidence: 99%
“…A fundamental understanding of the underlying structural mechanisms behind the catalytic activity of this enzyme has been established through extensive structural analysis of bacterial UPPs, starting with E. coli UPP (EcUPP) [13][16] and then the closely-related S. typhimurium homologue [17][19]. More recently, multiple structures of the human enzyme, hUPP1 [20], its bovine homologue, bUPP1 [21], and a UPP from the parasitic protozoa, Trypanosoma brucei [22], have been determined.…”
Section: Introductionmentioning
confidence: 99%
“…The conformation of 2,2'-O-anhydrouridine is high-syn (χ = 111 • ) with P~230 • . This conformation is observed in all three active sites in complexes with Salmonella typhimurium UP (PDB 3FWP) [53] and it is determined by the C2'-O-C2 covalent bond. The rigid structure of 2,2'-O-anhydrouridine is well accommodated by the active site of uridine phosphorylase.…”
Section: Conformations Of Nucleosides and Their Analogues In The Actimentioning
confidence: 98%